DOI: 10.14711/thesis-b1116248
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanisms of magnesium potassium phosphate cement and its application

Abstract: My sincere thanks to all the people who have contributed to this thesis during the last four years. My deepest gratitude goes first and foremost to Prof. Zongjin Li, my supervisor, for his constant encouragement and supports, valuable ideas and suggestions. Without his consistent and illuminating instruction, this thesis could not have reached its present form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…The results revealed that Area 1 was rich in B, O, Mg, P, and K with corresponding atom percentages of 21.38%, 50.92%, 11.06%, 6.21%, and 10.34%, respectively, wherein the ratio of atoms between K and Mg was close to 1:1, which was the theoretical ratio of K-struvite. Thus, the poor MPC water resistance and the decreased strength after water immersion was due to a large amount of gap in the sample interior resulting from the massive dissolution of MgO and K-struvite in the MPC hydrate of water immersion curing, which was in accordance with previous findings [3].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results revealed that Area 1 was rich in B, O, Mg, P, and K with corresponding atom percentages of 21.38%, 50.92%, 11.06%, 6.21%, and 10.34%, respectively, wherein the ratio of atoms between K and Mg was close to 1:1, which was the theoretical ratio of K-struvite. Thus, the poor MPC water resistance and the decreased strength after water immersion was due to a large amount of gap in the sample interior resulting from the massive dissolution of MgO and K-struvite in the MPC hydrate of water immersion curing, which was in accordance with previous findings [3].…”
Section: Resultssupporting
confidence: 91%
“…Magnesium phosphate cement (MPC) is a water-hardening inorganic cementitious material [1,2,3]. Compared with the conventional Portland cement, MPC has different chemical reaction, product, and performance.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Wagh and co-workers have studied the chemical reactions between phosphoric acid or acidic phosphates and various oxides that produce CBPCs; they used solution chemistry and thermodynamics to elucidate the synthesis of CBPCs and produced magnesium phosphate cements, 14 aluminum phosphate cement, 15 and iron phosphate cement. 16 Among phosphate cements, magnesium phosphate cements (MPCs) have attracted the most attention and have been the focus of research, especially for their performance, [17][18][19][20] formation mechanisms, 21,22 and applications. However, to formulate MPCs, the magnesium oxide needs normally to be dead-burned at a temperature of 1300°C-1700°C to increase the setting time.…”
mentioning
confidence: 99%
“…Magnesium ions slowed down the brushite setting reaction and also formed newberite (MgHPO4•3H2O) as a second setting product. In other studies [117] it is observed that excessive magnesium oxide residues lead to high pH and poor biocompatibility. Goldberg et al [118] studied the influence of [Ca+Mg]/P ratio on mechanical properties of calcium magnesium phosphates cements.…”
Section: Resorbability Of Phosphate-based Biomaterials With Different Ca/mg Ratiosmentioning
confidence: 88%